ANALISIS NILAI TAMBAH USAHA EMPING GARUT (Studi Kasus Agroindustri Raflesia Emping Garut di Desa Ngasem Kabupaten Bojonegoro): (Studi Kasus Agroindustri Raflesia Emping Garut di Desa Ngasem Kabupaten Bojonegoro) - Furuhita, Fitri Aulia; Mubarokah; Andrian Syah, Mirza (Universitas Medan Area, 2024)
Raflesia Agroindustry is a business that processes arrowroot tubers into arrowroot chips. With the Raflesia agroindustry that changes the form of arrowroot tubers into new products with higher economic value after going through the processing process, it can provide added value and form a new price that is higher than without going through the processing process. This study aims to analyze the added value obtained from the Raflesia arrowroot puffing agroindustry, and formulate efforts to increase the income of the Raflesia agroindustry. There were 8 informants as respondents in this study. Data analysis used to calculate added value using the Hayami method, and to formulate efforts to increase business income using the Business Model Canvas (BMC). The results showed that the calculation of added value from processing arrowroot tubers into arrowroot chips obtained a result of Rp 2,972/kg with a value-added ratio of 25%. In an effort to increase the income of the Raflesia arrowroot emping agro-industry by designing alternative Business Model Canvas (BMC) including target markets in adolescence, adding flavor variants, utilizing Instagram and Tiktok social media, providing purchase discounts, using technology, product renewal, and working with the government. The implication of this research is in the form of efforts to increase income in the Raflesia arrowroot puffing agro-industry so that it grows more widely